2023
DOI: 10.1002/slct.202204845
|View full text |Cite
|
Sign up to set email alerts
|

Copper (I) Catalysed Tandem C−C and C−N Bond Cleavage of N‐Fused Imidazoles towards the Synthesis of N‐pyridinylamides

Abstract: Copper(I) catalysed oxidative conversion of imidazopyridines into N‐pyridinylamides has been achieved via tandem C−C and C−N bond cleavages under oxidative reaction conditions. The methodology has wide substrate scope and products were formed in good to excellent yields. This method is suitable for the oxidative conversion of both C‐3 functionalized as well as non‐functionalized imidazopyridines

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…On the other hand, N -(pyridin-2-yl)­amides have received extensive attention in recent years owing to their attractive biological properties, and hence a few elegant methods have been developed for their synthesis . Liu et al reported the synthesis of N -(pyridin-2-yl)­amides from ketones and 2-aminopyridines via direct oxidative C–C bond cleavage promoted by TBHP/TBAI or I 2 /TBHP .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, N -(pyridin-2-yl)­amides have received extensive attention in recent years owing to their attractive biological properties, and hence a few elegant methods have been developed for their synthesis . Liu et al reported the synthesis of N -(pyridin-2-yl)­amides from ketones and 2-aminopyridines via direct oxidative C–C bond cleavage promoted by TBHP/TBAI or I 2 /TBHP .…”
Section: Introductionmentioning
confidence: 99%